The genus Loxosceles Heineken & Lowe 1832 (Araneae: Sicariidae) in Colombia, with description of new cave-dwelling species - Cala-Riquelme, Franklyn; Gutiérrez-Estrada, Miguel A.; Daza, Eduardo Flórez (Zootaxa, 2015)
The genus Loxosceles Heineken & Lowe, 1832, the so-called brown or violin spiders, currently includes 107 species distributed in the subtropical-areas and tropics of Europe, Africa, Asia, Australia and America (World Spider Catalog 2015). Species of this genus may live in both natural habitats (under rocks, trunks, inside tree holes and caves) and inside houses (Gertsch 1967; Bertani et al. 2010). Loxosceles is a group of medical importance in several regions of the world, due to the large number of cases of envenomation registered annually (Swanson & Vetter 2006; Vetter 2008; Vetter et al. 2009). Gertsch (1967, 1983) conducted the most comprehensive revisions for Loxosceles in America, and proposed several species groups. More recently, the genus has been the focus of several studies including taxonomic revisions, phylogenetic analyses and biogeography (Duncan et al. 2010; Bertani et al. 2010; Gonçalves-de-Andrade et al. 2012; Lotz 2012; Sánchez-Ruiz & Brescovit 2013; Planas & Ribera 2014; Binford et al. 2008).